PESAN MORAL DAN GAYA BAHASA DALAM GRAFFITI DI KALIMANTAN TIMUR - Asmah Alawiyah; Nurliani Maulida; Kiftian Hady Prasetya (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2019)
The focus of the problem in this study is motivated by the rise of the graffiti phenomenon which contains moral messages to be conveyed by graffiti artists in East Kalimantan, especially in Balikpapan City, Samarinda City, Bontang City, and Kutai Kartanegara District. The purpose of this study was to determine the moral message conveyed in the use of language styles on graffiti in East Kalimantan. This research uses descriptive qualitative method with a sociolinguistic approach. Research data in the form of written text from graffiti data sources in East Kalimantan. Data collection techniques using the stages of observation, study documentation, and interviews. Research instruments in the form of cellphones, stationery, notebooks, and moral style indicator message tables in Graffiti Language. The results found an attachment between language style and moral messages to be conveyed by graffiti makers found 30 data. Research findings include: (1) Religious moral messages, with indicators of submission to God, prayer in earnest, requests for guidance in life, repentance to God, confession of wrongdoing for sin, gratitude, patience, and sincerity. (2) Social moral messages, with indicators relating to human values, mutual respect, mutual cooperation, tolerance, caring, solidarity, and integrity. (3) Individual moral messages, with indicators that include values ​​of obedience, humility, caution in acting, honesty, confidence, accuracy, and wisdom. The conclusion of the study found the use of conflicting language style to be the dominant language style used to express the taste, intention, and work of graffiti makers. Choice of language style in graffiti has a tendency to the style of irony, satire, and sarcasm. Moral messages in graffiti are often accompanied by pictures as illustrations and are implied so that it requires careful observation and in-depth understanding to find out the message to be conveyed by graffiti makers.